JAMUR Mycosphaerella musicola PATOGEN BERCAK DAUN PADA PISANG RUTAI (Musa borneensis) - Iin Arseni; Tutik Nugrahini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Although bananas grown in almost all developing countries in the world, there is rarely a research on bananas.  Though the prospect of bananas in Indonesia is enormous, both for domestic consumption and for export.  It is unfortunate that the current area of development of banana cultivation has declined because of the disease, include leaf spot.Until now, information about leaf spot fungus pathogens that cause disease on Rutai banana plants still lacking.This research aims to determine the fungal pathogens of leaf spot on Rutai banana plants.Research conducted in the laboratory of Pests and Diseases of the Faculty of Agriculture, University of Widyagama Mahakam Samarinda.The results showed that: (1) leaf spot disease that were found in Rutai banana plants caused by a group of fungi; and (2) identification of pathogenic fungi on the leaf spot was Mycosphaerella musicola and it had potential as leaf spot pathogen on Rutai banana plants.